(untitled) (Comprehensive Journal of Science, 2025)
The plastic image is an exciting language that harmonizes and dialogues with the visual schools of the recipient, and producing it is an art based on various plastic elements such as image, word, rhythm, line, and others. The plastic image is the most important element supporting theformulation of the design. It is the effective mental language and the strongest expression of the content of the work. The plastic image, represented by drawings and pictures, is one of the easiest cognitive expressive forms that the recipient can deal with and interact with, and the impact of these works on the recipient varies, and this variation is due to the ability of the recipient to contain and translate these works visually and intellectually. The importance of the image is that it is the first interface and defining identity, which is an effective intellectual medium that reflects the artistic trends of the work. Therefore, artistic trends, the plastic image, is one of the most important creative and intellectual aspects that effectively affect societies, and it is also one of the most important modern means of communication and the most common and communicative among the audience .